Strengths, opportunities, aspirations, and results: An emerging approach to organization development. Issue 1 (January 2017) - Zarestky, Jill; Cole, Catherine S.
Abstract: Organization development (OD) interventions have typically relied on the strengths, weaknesses, opportunities, and threats (SWOT) framework for strategic planning. The strengths, opportunities, aspirations, and results (SOAR) framework is a relatively new innovation in OD that may serve as a viable alternative to SWOT for those who wish to apply an appreciative inquiry approach. This paper presents the results of a scoping study in which the limited but varied literature support for SOAR is reviewed. An extensive search uncovered 27 publications pertaining to SOAR, which were then analyzed chronologically and thematically. Although findings include an overwhelmingly positive appraisal of SOAR, many gaps were uncovered in the literature and research regarding empirical support for the framework.